Ehrlichia‐induced hemophagocytic lymphohistiocytosis after autologous stem cell transplant. Issue 4 (30th April 2021) - Mitma, Angel A.; Burgess, Mary J.; van Rhee, Frits
Abstract: Hemophagocytic lymphohistiocytosis (HLH) causes multiorgan failure due to the release of multiple cytokines mediating widespread inflammation. We present a patient with multiple myeloma on maintenance chemotherapy with the anti‐CD38 monoclonal antibody daratumumab after autologous stem cell transplant (ASCT) who developed fatal HLH secondary to Ehrlichiosis.